Flavor changes in Lentinus Edodes enzymatic hydrolysate maillard reaction products with different sugars by gas chromatography‐ion mobility spectrometry - Wenjia Cui; Peiji Liu; Houli Liu; Yifei Sun; Wenliang Wang (Journal of Future Foods, 2023)
The characteristic flavor of the enzymatic hydrolysate of Lentinus edodes, which was involved in the Maillard reaction by xylose, fructose, glucose, sucrose, mannose, maltose, vitamin C (VC) and L-arabinose, was determined and analyzed by gas chromatography-ion mobility spectroscopy (GC-IMS). The characteristic flavor fingerprints of Maillard reaction products (MRPs) of L. edodes enzymatic hydrolysate were constructed. The differences in the characteristic flavors of Maillard reaction with different reducing sugars and VC were compared. The main characteristic flavor, characteristic peak, characteristic marker substance and content were determined, a principal component analysis (PCA) of volatile organic compounds (VOCs) was carried out. The results showed that there were 42 kinds of monomers and some dimers of volatile compounds in the samples including 17 aldehydes, 5 alcohols, 7 ketones, 2 esters, 2 acids, 7 other compounds and 2 ethers. The volatile VOCs of the sample with added sucrose, VC and L-arabinose were significantly higher than those of the enzymatic hydrolysate of L. edodes. After the Maillard reaction, the flavor of the hydrolysate was significantly improved, and the main components changed significantly.